2017
DOI: 10.1007/s10198-017-0879-5
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of vedolizumab compared with infliximab, adalimumab, and golimumab in patients with ulcerative colitis in the United Kingdom

Abstract: Our model predicted that treatment with vedolizumab improves QALY, increases time in remission and response, and is a cost-effective treatment option compared with all other biologics for biologic-naïve patients with moderately to severely active UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 24 publications
2
52
0
3
Order By: Relevance
“…Our findings are consistent with two recent cost-effectiveness analyses in the UK and Spain that examined VDZ compared with ADA, GOL, and IFX for the treatment of patients with moderate-to-severe UC who were anti-TNF-naïve [18,19]. Both studies also showed that long-term treatment with VDZ was associated with greater QALYs compared with ADA, GOL, and IFX [18,19]. In the UK analysis, the time horizon was 30 years as a proxy for lifetime, and VDZ was dominant over GOL and IFX and cost-effective compared with ADA [18].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings are consistent with two recent cost-effectiveness analyses in the UK and Spain that examined VDZ compared with ADA, GOL, and IFX for the treatment of patients with moderate-to-severe UC who were anti-TNF-naïve [18,19]. Both studies also showed that long-term treatment with VDZ was associated with greater QALYs compared with ADA, GOL, and IFX [18,19]. In the UK analysis, the time horizon was 30 years as a proxy for lifetime, and VDZ was dominant over GOL and IFX and cost-effective compared with ADA [18].…”
Section: Discussionsupporting
confidence: 91%
“…Both studies also showed that long-term treatment with VDZ was associated with greater QALYs compared with ADA, GOL, and IFX [18,19]. In the UK analysis, the time horizon was 30 years as a proxy for lifetime, and VDZ was dominant over GOL and IFX and cost-effective compared with ADA [18]. The analysis from Spain used a time horizon of 10 years [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wilson et al examined the clinical and economic impact of VDZ compared with IFX, ADA, and golimumab in the treatment of moderately to severely active UC in the United Kingdom. 71 Compared with the other biologics, VDZ was the more effective treatment. When considering costs and a lifetime time horizon, VDZ was dominant (more effective and less costly) compared with all other biologics.…”
Section: Place In Therapymentioning
confidence: 99%